AN ANALYSIS ON TRANSLATION METHODS’ PREFERENCE IN MEMOIR TRANSLATIONS PUBLISHED BY WARUNGSATEKAMU - Wijaya, Tomi (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2018)
This study investigates the general translation methods preference in memoir translations published by Warungsatekamu until April 2018 and what are the features of each translation method. This study uses translation method categories proposed by Newmark (1988). The data are twelve memoir translation texts which originally were written in English, and had been translated by Warungsatekamu’s translator into Indonesian. The result of translation methods analysis shows that there are seven translation methods applied. They are communicative translation method, free translation method, idiomatic translation method, faithful translation method, semantic translation method, word-for-word translation method and literal translation method. What influences these seven methods to be applied are the specific features of each translation methods.